Whole-body MRI in children: Would a 3D STIR sequence alone be sufficient for investigating common paediatric conditions? A comparative study. Issue 88 (March 2017) - Merlini, Laura; Carpentier, Marc; Ferrey, Solène; Anooshiravani, Mehrak; Poletti, Pierre-Alexandre; Hanquinet, Sylviane
Abstract: Objectives: To test the performance of a single 3D IR T2-Weighted sequence compared to a Whole-body MRI protocol including DWI, T1-Weighted and STIR 3D IR (3S) in a pediatric population. Methods: Two radiologists (15 and 30 years of experience), reviewed WBMRIs: first the STIR alone and 2 weeks later the 3S protocol. The indications were variable. Only positive findings were explicitly reported. A third reader compared the results to gold standard (GS) exams specific for the pathology. Agreement between the two readers, sensitivity and positive predictive value of STIR were calculated. Results: fifty-four WBMRIs were included (16 suspected child abuse, 8 chronic recurrent multifocal osteomyelitis (CRMO), 11 lymphomas, 4 osteosarcomas, 9 neuroblastomas, 6 histiocytosis). The mean age was 6 years 10 months, range: 1 month to 15 years. Agreement between readers was of 0.87 [0.82–0.91] for 3D STIR, and 0.89 [0.83–0.93] for the 3S protocol. For reader 1 sensitivity of 3D STIR was 81.6% and of 3S 81.0%. For reader 2 it was 74.1% for 3D STIR and 74.7% for 3S. For both readers and for both protocols, the positive predictive value (PPV) depended on the type of disease (for example 100% histocytosis and osteosarcomas, >90% for child abuse, >85% CRMO but <70% for lymphoma and neuroblastoma). Conclusions: Sensitivities were not different between the 2 protocols, for each reader and were different between the 2 readers for each protocol.